2020
DOI: 10.1101/2020.07.24.20161471
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiological and cohort study finds no association between COVID-19 and Guillain-Barré syndrome

Abstract: Background Reports of Guillain-Barre Syndrome (GBS) have emerged during the Coronavirus Disease 2019 (COVID-19) pandemic. This epidemiological and cohort study sought to investigate any causative association between COVID-19 infection and GBS. Methods The epidemiology of GBS cases reported via the UK National Immunoglobulin Database were studied from 2016-2019 and compared to cases reported during the COVID-19 pandemic. For the cohort study, members of the British Peripheral Nerve Society reported all case… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
104
3

Year Published

2021
2021
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(118 citation statements)
references
References 24 publications
11
104
3
Order By: Relevance
“…A similarly increased risk for stroke relative to influenza was recently reported. 25 Whether COVID-19 is associated with Guillain-Barre syndrome has been unclear; 26 our data indicate that the incidence is increased in hospitalized and encephalopathic patients, but not significantly in the whole cohort. There have been concerns about post-COVID-19 Parkinsonian syndromes, driven by the encephalitis lethargica epidemic that followed the 1918 influenza pandemic.…”
Section: Discussionmentioning
confidence: 65%
“…A similarly increased risk for stroke relative to influenza was recently reported. 25 Whether COVID-19 is associated with Guillain-Barre syndrome has been unclear; 26 our data indicate that the incidence is increased in hospitalized and encephalopathic patients, but not significantly in the whole cohort. There have been concerns about post-COVID-19 Parkinsonian syndromes, driven by the encephalitis lethargica epidemic that followed the 1918 influenza pandemic.…”
Section: Discussionmentioning
confidence: 65%
“…Recent studies in this and other journals [ 2 4 ] indicate an association. However others did not find any epidemiological evidence so far [ 1 ]. In this latter study, no significant association between COVID-19 and GBS was found.…”
mentioning
confidence: 99%
“…In this latter study, no significant association between COVID-19 and GBS was found. In 47 patients with GBS (of those 13 patients with definite, 12 with probable, and 22 patients without COVID-19) there was no atypical pattern in incidence, clinical presentation or response to established therapies in COVID-19 associated GBS [ 1 ]. Uniquely, a higher rate of assisted ventilation requirement was observed in GBS subsequent to COVID-19 [ 1 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these patients required ventilatory support and immunoglobulin treatment [ 2 9 ]. Recent studies support the association between GBS and COVID-19 [ 10 , 11 ], although one analysis did not find this association [ 12 ].…”
Section: Introductionmentioning
confidence: 99%